Effect of Design Parameter Variations on the Quality Factor of a Microring Resonator Filter - Haroon, Hazura; Hanim , Abdul Razak; Mardiana, Bidin; Shaari, Sahbudin; Majlis, B.Y; Menon, P.S (2013)
We present the design and optimization results for a Silicon-on-Insulator (SOI) waveguide microring resonator (MRR) filter by Finite Difference Time Domain (FDTD) simulations. The effect of parameter variations on the Q-factor of the MRR filter was investigated by applying Taguchi Method. Four control factors were considered, ring radii, separation gap between the bus waveguide and the ring waveguide, waveguide width and upper rib height as well as two noise factors ie rib surface roughness and slope angle. The influence of each design parameter on the Q-factor characteristic was determined using analysis of variance (ANOVA) and the simulation was performed using Fullwave software from RSoft. The performance of the optimized design was then evaluated and the best MuQ-factor value obtained was 1050. Optimization using Taguchi method provides a cost-effective method to produce robust device designs prior to the actual fabrication.